The Impact of COVID-19 on Frozen Meat Business Operators in the Tamale Metropolis of Ghana - Monten, Stephen K.K.; Adzitey, Frederick (Al-Nahrain Journal of Science, 2020)
This study determined the impact of COVID-19 among frozen meat business operators in the Tamale metropolis, Ghana. A semi-structured questionnaire was used to collect data from 65 frozen meat business operators/respondents. The results showed that, most of the respondents had secondary education (50.8%), engaged in the business on full time (84.6%) and started it with their own capital (96.9%). COVID-19 had a negative impact on respondents (73.8%), most importantly low sales (64.6%). This was due to financial challenges of clients/customers (43.1%) and close-down of the hospitality industry (20.0%). Three of the respondents laid off workers due to COVID-19. Some (24.6%) of the respondents were not prepared for COVID-19 because they least expected it will cause such crises. Their businesses will collapse (44.6%) or they will close down their business themselves (43.1%) if lockdown due to COVID-19 lasts for more than 5 months. The respondents suggested the reduction of tax at the harbour (69.2%) as a potential means of assisting them during COVID-19 and massive reduction in the price of meat (41.3%) as a means of assisting their business post COVID-19. The study concludes that COVID-19 had negative effect on frozen meat operators in Tamale, Ghana.